Aspidistra nikitensis (Asparagaceae, Nolinoideae), a new species from Vietnam - Kalyuzhny, Sergey S.; Vislobokov, Nikolay A.; Luu, Hong Truong; Plugatar, Yury V.; Kuznetsov, Andrey N.; Kuznetsova, Svetlana P.; Korzhenevsky, Vladislav V.; Vin’kovskaya, Oksana P. (Phytotaxa, 2022)
Aspidistra nikitensis is described and illustrated as a new species from Gia Lai province of Vietnam. The new species possesses linear leaves and trimerous flowers with a mushroom-shaped pistil. In these features, the new species is morphologically similar to A. hainanensis species complex but differs in its convex stigma with projections. In stigma structure, A. nikitensis resembles A. longanensis but differs in shape of leaves and flower merism.